Proses Perbaikan Plate Heat Exchanger Tipe M15 di PT. Janata Marina Indah (JMI) Semarang - Adi Kurniawan Yusim; Budi Utomo; Suharto Suharto; Hartono Hartono (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
Most of the heat exchangers onboard are in the form of shell and tube. Another form is the plate heat exchanger (PHE). The advantage of PHE is that it has a very large displacement surface at a small volume of tools. Selection of suitable gasket material for PHE is very important. It is intended for a long service life of PHE. The research has been conducted at the shipyard of PT. JMI Semarang to find out the location and cause of plate leakage from PHE. PHE observations and improvements are carried out when the ship is docked at the shipyard. Repairs were made directly in the form of operational data and manual book PHE type of M15.